Design of a data converter physical unclonable function - Wu, Jie Kai (2017)
Security has been a key area of interest in the current world of information technology. Cryptography is widely used in information protection schemes by generating secret keys or authentication. As technology advances, it is difficult and costly to preserve the secret keys in non-volatile memory securely and information data may eventually be compromised. Physical Unclonable Function (PUF) is an emerging security primitive that exploits the uncontrollable process variations, which is inherent in Integrated Circuit (IC) instance manufacturing, for secret generation and storage, as well as device identification and authentication. Recently, many types of PUFs have been proposed, including the most popular Arbiter PUF, Ring Oscillator PUF and SRAM based PUF. However, as most of the PUFs are implemented as a separate module, they may induce large area overhead. A better alternative is design the circuit for both normal function as well as additional PUF function. Mixed Signal data converters, as an essential component in integrated circuitry, are used in a wide variety of applications including audio appliances, camera etc. However, no one has exploits the possibilities to use them as an PUF. Implementing ADC or DACs as PUF provides a promising alternative to ensure its data integrity. This report, for the first time, exploits the process variation existing in the data converters. Non-ideal properties on ADC and DAC have been analyzed and statistical analysis has been done to evaluate its performance as a PUF.